2018
DOI: 10.1021/acsami.8b18891
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Proton-Conductive 3D Ionic Cadmium–Organic Framework for Ammonia and Amines Impedance Sensing

Abstract: Lately, the progressive study of metal−organic frameworks (MOFs) for the detection of ammonia and amines has made infusive achievements. Nevertheless, the investigation of proton-conductive MOFs used to detect the low concentrations of ammonia and amine gases at different relative humidities (RHs) at room temperature is relatively restricted. Herein, by solvothermal reaction of Cd(NO 3 ) 2 with 2-methyl-1H-imidazole-4,5-dicarboxylic acid (H 3 MIDC), a three-dimensional ionic MOF {Na[Cd(MIDC)]} n (1) bearing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 69 publications
2
49
0
Order By: Relevance
“…At 25 8C, the data from the Nyquist plots reveal that the low protonc onductivity of 1 (2) ranges from 1.19 10 À7 (2.13 10 À8 )t o4 . 47 1 (2), the protonc onductivity increased from 6.54 10 À5 (5.18 10 À5 )Scm at 68 %R Ht o1 .31 10 À4 (1.16 10 À4 )Scm at 85 % RH, then reached the highest proton conductivity of 1.04 10 À3 (7.02 10 À4 )Scm at 98 %RH (Figures 3c and S20, Table S7 in the Supporting Information). As denoted in Table S8 (in the Supporting Information), these conductivity values of 1 and 2 can be compared with that of several renowned MOFs under similar testing conditions, [12,13,[38][39][40] such as {[Co 3 (m-ClPhID-C) 2 (H 2 O) 6 ]·2H 2 O} n (m-ClPhH 3 IDC = 2-(m-chlorophenyl)imidazole-4,5-dicarboxylic acid; s = 7.62 10 À4 Scma t1 00 8C), [13] Mg-BPTC (BPTC = 2,2',6,6'-tetracarboxybiphenyl; s = 2.6 10 À4 Scm at 100 8Ca nd 98 %R H), [12]…”
Section: Resultsmentioning
confidence: 96%
“…At 25 8C, the data from the Nyquist plots reveal that the low protonc onductivity of 1 (2) ranges from 1.19 10 À7 (2.13 10 À8 )t o4 . 47 1 (2), the protonc onductivity increased from 6.54 10 À5 (5.18 10 À5 )Scm at 68 %R Ht o1 .31 10 À4 (1.16 10 À4 )Scm at 85 % RH, then reached the highest proton conductivity of 1.04 10 À3 (7.02 10 À4 )Scm at 98 %RH (Figures 3c and S20, Table S7 in the Supporting Information). As denoted in Table S8 (in the Supporting Information), these conductivity values of 1 and 2 can be compared with that of several renowned MOFs under similar testing conditions, [12,13,[38][39][40] such as {[Co 3 (m-ClPhID-C) 2 (H 2 O) 6 ]·2H 2 O} n (m-ClPhH 3 IDC = 2-(m-chlorophenyl)imidazole-4,5-dicarboxylic acid; s = 7.62 10 À4 Scma t1 00 8C), [13] Mg-BPTC (BPTC = 2,2',6,6'-tetracarboxybiphenyl; s = 2.6 10 À4 Scm at 100 8Ca nd 98 %R H), [12]…”
Section: Resultsmentioning
confidence: 96%
“…It is speculated that the rich hydrogen bonding interaction between the imidazole Na toms,w ater molecules and formic acid molecule plays ac rucial role in selectivity.H ydrogen bonds are ubiquitous in various chemicals and biological systems, [56][57][58][59] where ploargroups, [60,61] such as -CO-NH 2 and -COOH groups, can be very close to each other and undergo exceptionally strong electrostatic interactions. [10,20,33,35] A large number of literatures have found that the employment of hydrogen bond interaction to perform chemical selectivity in the field of molecular identification and sensingh as been extensively researched. Based on the investigation of proton conductivity of impedances ensing for ammonia and amine, it is found that the structurec haracteristics of MOF and detection gas have a great influenceo nt he recognition performance.…”
Section: Resultsmentioning
confidence: 99%
“…[5,16,[25][26][27][28] On the other hand, based on the outstanding advantagesofMOFs, the exploration of the practical application of electrically conductive MOFs has received extensive attention, especially in the field of chemoresistive sensors. [29][30][31][32][33][34] Representatively,D incǎ et al demonstrated an array of cross-reactive sensor for the identification of different typeso fv olatile organic compounds (VOCs). [34] Nevertheless, the studies on proton conductingM OFs as sensors are very limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations